Rapid Generation of Multiple Loci-Engineered Marker-free Poxvirus and Characterization of a Clinical-Grade Oncolytic Vaccinia Virus - Zong Sheng Guo (Molecular Therapy: Methods & Clinical Development, 2017)
Recombinant poxviruses, utilized as vaccine vectors and oncolytic viruses, often require manipulation at multiple genetic loci in the viral genome. It is essential for viral vectors to possess no adventitious mutations and no (antibiotic) selection marker in the final product for human patients in order to comply with the guidance from the regulatory agencies. Rintoul et al. have previously developed a selectable and excisable marker (SEM) system for the rapid generation of recombinant vaccinia virus. In the current study, we describe an improved methodology for rapid creation and selection of recombinant poxviruses with multiple genetic manipulations solely based on expression of a fluorescent protein and with no requirement for drug selection that can lead to cellular stress and the risk of adventitious mutations throughout the viral genome. Using this improved procedure combined with the SEM system, we have constructed multiple marker-free oncolytic poxviruses expressing different cytokines and other therapeutic genes. The high fidelity of inserted DNA sequences validates the utility of this improved procedure for generation of therapeutic viruses for human patients. We have created an oncolytic poxvirus expressing human chemokine CCL5, designated as vvDD-A34R-hCCL5, with manipulations at two genetic loci in a single virus. Finally, we have produced and purified this virus in clinical grade for its use in a phase I clinical trial and presented data on initial in vitro characterization of the virus.